Systematic Review of the Relationship between Hygiene Practice and the Incidence of Ascaris lumbricoides Infection in Southeast Asian Children - Alodia, Anastasia Rouli; Wulandari, Ririn Arminsih (Universitas Negeri Malang, 2023)
Soil-Transmitted Helminth (STH) infection is one of the Neglected Tropical Diseases (NTDs) that affects around 1.5 billion people worldwide, including regions like Southeast Asia. The most common species infecting humans is Ascaris lumbricoides. Preschool-age and school-age children are particularly vulnerable to STH infection due to their living environments in areas where STH is prevalent. Infection of STH, especially Ascaris lumbricoides, can hinder physical and cognitive development and, in severe cases, cause obstruction of the small intestine. Various factors, such as hygiene practices, can influence the transmission of Ascaris lumbricoides infection in children. This study aims to explore the association between hygiene practices and the occurrence of Ascaris lumbricoides infection in children. A systematic review was carried out, and articles were searched in four databases: PubMed, EMBASE, Scopus, and ProQuest. Subsequently, the articles were selected based on specific criteria. Five articles were identified during the search. These articles revealed a significant association between handwashing habits, toilet usage, and washing fruits before consumption with the occurrence of Ascaris lumbricoides infection. On the other hand, there was no significant association found between washing vegetables before consumption and trimming nails and the occurrence of Ascaris lumbricoides infection in children.